Excusing Economic Envy: On Injustice and Impotence. Issue 2 (14th March 2016) - Bankovsky, Miriam
Abstract: From the Ancient Greeks, through medieval Christian doctrine, and into the modern age, philosophers have long held envy to be irrational, a position that increasingly accompanies the political view that envy is not a justification for redistributing material goods. After defining the features of envy, and considering two arguments in favour of its irrationality, this article opposes the dominant philosophical and political consensus. It does so by deploying Rawls's much‐ignored concept of 'excusable envy' to identify a form of envy that is not imprudent and does not mis‐describe. With this work completed, the article then argues – no doubt controversially – that excusable envy constitutes good grounds for redistribution or inequality‐mitigation. In so doing, the article throws light on the moral significance of certain forms of uncivil disobedience, and also offers a new vocabulary for popular 'politics of envy' debates, which are yet to acknowledge the role of social institutions in reproducing envy‐excusing economic inequalities.